A field guide to mortar sampling for radiocarbon dating*. (11th January 2021) - Daugbjerg, T. S.; Lindroos, A.; Heinemeier, J.; Ringbom, Å.; Barrett, G.; Michalska, D.; Hajdas, I.; Raja, R.; Olsen, J.
Abstract : Radiocarbon dating of mortars is a method for absolute dating of historical mortared stone structures. Successful mortar dating studies have answered chronological questions, while other studies have revealed that mortar samples can have complications and contaminants. These can cause inconclusive results even with present state‐of‐the‐art techniques. Previous research shows that adequate and proper sampling of mortar samples is of fundamental importance for a conclusive radiocarbon analysis. Therefore, this article thoroughly reviews the processes and environmental factors that may cause problems for successful radiocarbon dating of mortar samples, and presents best‐practice sampling strategies for radiocarbon mortar dating.